KLF2 is a therapeutic target for COVID-19 induced endothelial dysfunction - Xu, Suowen; Luo, Sihui; Zheng, Xueying; Weng, Jianping (bioRxiv, 2021)
Abstract Coronavirus disease 2019 (COVID-19) is regarded as an endothelial disease (endothelialitis) with its mechanism being incompletely understood. Emerging evidence has demonstrated that the endothelium represents the Achilles' heel in COVID-19 patients and that endothelial dysfunction precipitates COVID-19 and accompanying multi-organ injuries. Thus, pharmacotherapies targeting endothelial dysfunction have potential to ameliorate COVID-19 and its cardiovascular complications. Primary human umbilical vein endothelial cells (HUVECs) and human pulmonary microvascular endothelial cells (HPMECs) were treated with serum from control subjects or COVID-19 patients. Downstream monocyte adhesion and associated gene/protein expression was evaluated in endothelial cells exposed to COVID-19 patient serum in the presence of KLF2 activator (Atorvastatin) or KLF2 overexpression by an adenoviral vector. Here, we demonstrate that the expression of KLF2 was significantly reduced and monocyte adhesion was increased in endothelial cells treated with COVID-19 patient serum due to elevated levels of pro-adhesive molecules, ICAM1 and VCAM1. IL-1β and TNF-α, two cytokines observed in cytokine release syndrome in COVID-19 patients, decreased KLF2 gene expression. Next-generation RNA-sequencing data showed that atorvastatin treatment leads to a cardiovascular protective transcriptome associated with improved endothelial function (vasodilation, anti-inflammation, antioxidant status, anti-thrombosis/-coagulation, anti-fibrosis and reduced angiogenesis). Treatment of HPMECs with atorvastatin or KLF2 adenovirus ameliorate COVID-19 serum-induced increase in endothelial inflammation and monocyte adhesion by increasing KLF2 expression. Altogether, the present study demonstrates that genetic and pharmacological activation of KLF2 represses COVID-19 associated endothelial dysfunction, heralding a potentially new direction to treat endothelialitis accompanying COVID-19. Competing Interest Statement The authors have declared no competing interest.